Charaterisation of a chitinase produced by an environmental Paenibacillus chitinolyticus strain PBY - Chhiba, Varsha Parshotam (My University, 2010)
An isolated environmental strain PBY when submitted for 16s rDNA analysis was shown to have 99% sequence similarity to Paenibacillus chitinolyticus sequence data by BLAST searching the sequence data obtained. The strain when induced in minimal media containing pure chitin was found to produce multiple chitinolytic enzymes by 2D polyacrylamide gel separation with pI‟s ranging from 4.8 to 5.3 and from 7.0 to 9.2. Further characterisation work done on the dominant extracellular chitinolytic enzyme (chitinase with a pI 7.0) showed that this enzyme is an endochitinase with a preference for longer chain substrates. The Km values when incubated with 4-MU CHB and 4-MU CHT being were found to be 7.45 μM and 5.72 μM respectively. The same chitinase enzyme when incubated with a trimeric substrate produced a dimer and GlcNAc as final products. The characterised extracellular enzyme showed optimum chitinase activity between pH 7.0 to 7.5 with 80% activity retained between pH 6.5 and 8.0. The optimum temperature range for the extracellular chitinase was found to be between 30oC and 40oC, while the purified chitinase maintained 80 to 90% of activity at temperatures ranging from 10oC to 50oC after an hour of incubation of the enzyme at the respective temperatures. The characterised chitinase enzyme maintained 50% activity after incubation for an hour at 65oC. This appears to be the first known P. chitinolyticus chitinase enzyme to be purified and characterised to date.